2013
DOI: 10.1038/ncomms3791
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale mechanisms of ferroelastic domain-wall-mediated ferroelectric switching

Abstract: Polarization switching in ferroelectric thin films occurs via nucleation and growth of 180°d omains through a highly inhomogeneous process in which the kinetics are largely controlled by defects, interfaces and pre-existing domain walls. Here we present the first real-time, atomic-scale observations and phase-field simulations of domain switching dominated by pre-existing, but immobile, ferroelastic domains in Pb(Zr 0.2 Ti 0.8 )O 3 thin films. Our observations reveal a novel hindering effect, which occurs via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
155
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(173 citation statements)
references
References 46 publications
18
155
0
Order By: Relevance
“…16 Significant charge concentrations can exist at 90º domain walls, which then exert a local pressure on 180º domain walls even at sub-switching electric fields due to variations in the local electric field. 17,18 Experimentally, PFM measurements demonstrated that 1-and 2-dimensional defects produce significant pinning of 180º domain walls in ferroelectric films. [19][20][21][22][23][24] The local electric field created by defects and domain wall -domain wall pinning are the major contributions to domain wall pinning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Significant charge concentrations can exist at 90º domain walls, which then exert a local pressure on 180º domain walls even at sub-switching electric fields due to variations in the local electric field. 17,18 Experimentally, PFM measurements demonstrated that 1-and 2-dimensional defects produce significant pinning of 180º domain walls in ferroelectric films. [19][20][21][22][23][24] The local electric field created by defects and domain wall -domain wall pinning are the major contributions to domain wall pinning.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23][24] The local electric field created by defects and domain wall -domain wall pinning are the major contributions to domain wall pinning. 17,25 It is widely reported that in tetragonal ferroelectrics the domain structures of adjacent grains are correlated due to local strain and electric fields. 2,26 Ivry et al…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies are qualitative and do not provide * cd@anl.gov direct quantitative information about, or images of, the polarization state of the ferroelectric. Recently, high resolution aberration-corrected TEMs have been employed to infer the ferroelectric polarization in PZT thin films by measuring atomic displacements and deviations from centrosymmetry at the unit cell level [9], or strain measurement using geometric phase analysis (GPA) [10] rather than by capturing the electric field that arises from polarization charges.…”
Section: Introductionmentioning
confidence: 99%
“…Switching of superdomains: Fig.10 shows the TEM photos of a ferroelastic superdomain switching large amounts of charge. [83] This shows that ferroelastic superdomains move as large coherent blocks in ferroelectric switching [31,[84][85][86][87] and hence that the switching dynamics are not dominated by reversal of nano-scale ferroelectric domains within these blocks, i.e. are not described by the Landau-Lifshitz-Kittel domain model.…”
mentioning
confidence: 99%
“…In addition to these two kinds of ferroelastic walls (mirror plane and twofold axis), more recently it has been shown that ferroelastic fourfold axes also exist. [44] These ferroelastic bundles switch as a block in some ferroelectrics, [45,46] resulting in hysteresis loops with very large steps. We emphasize this aspect of superdomains, because it will control ferroelectric switching in many thin-film devices, because most ferroelectric memory materials are also ferroelastic.…”
mentioning
confidence: 99%